Book review cuttings on the works of : Larry Pickering. (1978)
Book reviews from Australian newspapers and journals on the works of Australian authors. Files may contain original cuttings or references. Content covers the time period from the mid 20th century to 2000.
Keywords: Pickering, Larry; Books -- Australia -- Reviews; Authors, Australian -- 20th century; Australian